PENGARUH PROMOSI DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN TOKO KUE L’CHEESE FACTORY PEKANBARU - Adil Asyhadi Supma; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at the Pekanbaru L'cheese Cake Factory located at Jalan Durian No.28, Sukajadi, Kec. Sukajadi, Pekanbaru City, Riau 28121. The purpose of this study was to study the promotion and pricing of purchasing decisions on consumers of the L'cheese Factory Pekanbaru Cake Shop partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study were all consumers of L'cheese Factory Pekanbaru Pastry Shop products in the year 2018 totaling 1,500 people. Where the samples in this study were consumers of the L'cheese Factory Pekanbaru Cake Shop as many as 100 respondents. To determine the sample using the slovin formula, a non-probability sampling technique with accidental sampling technique. Data collection techniques through interviews and questionnaires, types and sources of data using primary data and secondary data, measurement techniques using a Likert scale.From data analysis using validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and F test (simultaneous). The results showed the results of the first t-test hypothesis, the promotion of consumer purchasing decisions, namely t arithmetic (9,557)> t table (1,660), which means a significant promotion of consumer purchasing decisions. second, pricing of consumer purchasing decisions, namely t arithmetic (10,700)> t table (1,660) means that the price setting affects significantly to consumer purchasing decisions. Test F results of promotions and pricing are significant to consumer purchasing decisions, namely F arithmetic (73.738)> F table (3.09). Associated with the promotion and pricing by simultaneous significant influence on consumer purchasing decisions in Pekanbaru L'cheese Factory Cake Shop.Keywords: Promotion, Pricing, Consumer Purchase Decisions